Electronic Component Mounting for Durable E-Textiles: Direct Soldering of Components onto Textile-Based Deeply Permeated Conductive Patterns - Koshi, Tomoya (Micromachines (Basel), 2020)
For the improvement of the performance and function of electronic textiles (e-textiles), methods for electronic component mounting of textile circuits with electrical and mechanical durability are necessary. This manuscript presents a component mounting method for durable e-textiles, with a simpler implementation and increased compatibility with conventional electronics manufacturing processes. In this process, conductive patterns are directly formed on a textile by the printing of conductive ink with deep permeation and, then, components are directly soldered on the patterns. The stiffness of patterns is enhanced by the deep permeation, and the enhancement prevents electrical and mechanical breakages due to the stress concentration between the pattern and solder. This allows components to be directly mounting on textile circuits with electrical and mechanical durability. In this study, a chip resistor was soldered on printed patterns with different permeation depths, and the durability of the samples were evaluated by measuring the variation in resistance based on cyclic tensile tests and shear tests. The experiments confirmed that the durability was improved by the deep permeation, and that the samples with solder and deep permeation exhibited superior durability as compared with the samples based on commercially available elastic conductive adhesives for component mounting. In addition, a radio circuit was fabricated on a textile to demonstrate that various types of components can be mounted based on the proposed methods.